2017
DOI: 10.15673/fst.v11i3.608
|View full text |Cite
|
Sign up to set email alerts
|

Дослідження Жирнокислотного Складу Ліпідів Сухих Рибо-Рослинних Напівфабрикатів

Abstract: Кафедра технології і організації ресторанного господарства Київський національний торговельно-економічний університет, вул. Кіото, 19, м. Київ, Україна, 02156 Анотація. Досліджено жирнокислотний склад ліпідів сухих рибо-рослинних напівфабрикатів на основі фаршів з бичка азово-чорноморського та суміші рослинних інгредієнтів (шротів насіння льону, висівок пшеничних, вівсяних та житніх), вивчено показники їхньої біологічної ефективності. Наведені експериментальні дані свідчать про значний вміст у розроблених н… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
2
0
1
Order By: Relevance
“…It was experimentally established that in the lipids of meat-containing semifinished products containing the meat of duck and silver Prussian carp the level of MUFA is 44.77 %, PUFA -22.16 %, saturated -31.12 %. The biological efficacy of lipids in food products is characterized not only by the number of MUFA and PUFA, but also by the ratio of ω-3 and ω-6 of PUFA, which, based on the recommended norms [33], must be from 1:4 to 1:10. It was established experimentally that the meat-containing minced semi-finished product demonstrated that the specified ratio was 1:7 due to the introduction to the formulation of duck meat and freshwater fish meat, which are distinguished by the high content of PUFA.…”
Section: Discussion Of Results Of Studying a Set Of Indicators For Thmentioning
confidence: 99%
“…It was experimentally established that in the lipids of meat-containing semifinished products containing the meat of duck and silver Prussian carp the level of MUFA is 44.77 %, PUFA -22.16 %, saturated -31.12 %. The biological efficacy of lipids in food products is characterized not only by the number of MUFA and PUFA, but also by the ratio of ω-3 and ω-6 of PUFA, which, based on the recommended norms [33], must be from 1:4 to 1:10. It was established experimentally that the meat-containing minced semi-finished product demonstrated that the specified ratio was 1:7 due to the introduction to the formulation of duck meat and freshwater fish meat, which are distinguished by the high content of PUFA.…”
Section: Discussion Of Results Of Studying a Set Of Indicators For Thmentioning
confidence: 99%
“…As a result of using freshwater fish and duck meat in the recipe, the biological efficiency of lipids of a meat-containing cut semi-product, characterized by the normative ratio of ω-3 and ω-6 PUFA [27,28], was 1:7. It testifies to the fact that at combining Pekin duck and freshwater fish, namely silver crucian in the composition of frozen cut meat-containing semi-products, it is possible to produce biologically full-value products with high qualitative characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…Визначення вмісту амінокислот у напівфабрикатах проводили методом іонообмінної колонкової хроматографії за допомогою амінокислотного аналізатора «BIOTRONIK» (Німеччина) [9]. Жирнокислотний склад визначали методом газорідинної хроматографії за допомогою автоматизованого газового хроматографа Купол-55 [10].…”
Section: ключові слова: напівфабрикати з м'яса м'ясо качки прісноводн...unclassified